DAKWAH DI RUANG VIRTUAL: OPTIMALISASI MEDIA SOSIAL DALAM PENYEBARAN PESAN ISLAM - Iswadi, Iswadi (Lembaga Sepercenter, 2024)
The development of digital technology has brought significant changes to the patterns of religious communication. Social media has now become a new space for preachers to convey Islamic messages more widely, quickly, and interactively. This risearch aims to analyse the role of social media in optimising religious communication in the digital era, highlighting opportunities, challenges, and effective communication strategies. The method used is a literature review, examining relevant literature on digital da'wah communication, social media, and the phenomenon of religious diversity in virtual spaces. The research findings indicate that social media can be an effective tool for expanding the reach of da'wah, building interaction with audiences, and enhancing Islamic literacy. However, on the other hand, dakwah in virtual spaces also faces challenges in the form of hoaxes, hate speech, and limited validity of information. Therefore, creative, ethical, and digital literacy-based communication strategies are needed so that dakwah on social media can have a significant positive impact.